Bleeding risk factors with enoxaparin for patients with NSTEMI/UA in HUKM - Noraida Mohamed Shah,; Rosnani Hashim,; Azmi Sarriff, (Penerbit UKM, 2008)
Low-molecular-weight heparins (LMWHs) are antithrombotic agents utilised in the treatment of acute coronary syndromes. They have been shown to be more effective than unfractionated heparins (UFHs) in reducing ischeamic e v e n t s , w h i c h i n c l u d e d e a t h , my o c a r d i a l i n f a r c t i o n (MI) a n d u r g e n t revascularisation. Enoxaparin is one of the products of LMWHs. Its safety and efficacy has been proven in the ESSENCE and TIMI IIB studies. This study was carried out to identify risk factors that may affect bleeding complications associated with the use of enoxaparin for non-ST-elevation MI (NSTEMI) or unstable angina (UA) in Universiti Kebangsaan Malaysia Hospital (HUKM). This observational, longitudinal study was conducted on patients who were admitted to the Coronary Care Unit (CCU), Coronary Rehabilitation Ward (CRW), Medical 1 and Medical 2 wards at HUKM and initiated on enoxaparin for NSTEMI/UA from 22 nd of March until 22 nd of April 2004. A total of 40 patients were included in the study with median age of 65 years, male to female ratio of 3:1, diagnosed with NSTEMI (55%) and UA (45%). 45% of patients developed an episode of bleeding and among them 83.3% (15 patients) characterised by haematuria. Higher percentages of women (80%) and those with creatinine clearance of < 30ml/min (100%) had incidence of bleeding as compared to men (50%) and those with creatinine clearance ≥ 30 ml/min, respectively (p < 0.05 for both parameters). Age, enoxaparin dose and duration of therapy, smoking and concomitant aspirin/ticlopidine therapy did not significantly affect the incidence of bleeding. In conclusion, renal impairment and gender were associated with bleeding in relation with the use of enoxaparin that may require dose adjustments.